2016
DOI: 10.1038/srep25911
|View full text |Cite
|
Sign up to set email alerts
|

Intermartensitic Transformation and Enhanced Exchange Bias in Pd (Pt) -doped Ni-Mn-Sn alloys

Abstract: In this work, we studied the phase transitions and exchange bias of Ni50−xMn36Sn14Tx (T = Pd, Pt; x = 0, 1, 2, 3) alloys. An intermartensitic transition (IMT), not observed in Ni50Mn36Sn14 alloy, was induced by the proper application of negative chemical pressure by Pd(Pt) doping in Ni50−xMn36Sn14Tx (T = Pd, Pt) alloys. IMT weakened and was suppressed with the increase of applied field; it also disappeared with further increase of Pd(Pt) content (x = 3 for Pd and x = 2 for Pt). Another striking result is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…As showed in Figure 2, evidence is found that the 2 2 0 peak/reflection shifts to a lower angle when we increase the substitution of Ni by Pd, leading to the growth of cell volume. Analogous behaviour was also observed in Ni 50−x Mn 36 Sn 14 Pd x samples [15], confirming that this effect is probably due to the substitution of larger Pd addition (1.79 Å) in previous Ni sites (1.62 Å). It is known that the characteristic martensitic start transformation temperature in Heusler samples is powerfully affected by the Mn-Mn interatomic distances [19].…”
Section: Xrd Analysissupporting
confidence: 75%
See 4 more Smart Citations
“…As showed in Figure 2, evidence is found that the 2 2 0 peak/reflection shifts to a lower angle when we increase the substitution of Ni by Pd, leading to the growth of cell volume. Analogous behaviour was also observed in Ni 50−x Mn 36 Sn 14 Pd x samples [15], confirming that this effect is probably due to the substitution of larger Pd addition (1.79 Å) in previous Ni sites (1.62 Å). It is known that the characteristic martensitic start transformation temperature in Heusler samples is powerfully affected by the Mn-Mn interatomic distances [19].…”
Section: Xrd Analysissupporting
confidence: 75%
“…Processes 2020, 8, x FOR PEER REVIEW 4 of 14 behaviour was also observed in Ni50−xMn36Sn14Pdx samples [15], confirming that this effect is probably due to the substitution of larger Pd addition (1.79 Å) in previous Ni sites (1.62 Å). It is known that the characteristic martensitic start transformation temperature in Heusler samples is powerfully affected by the Mn-Mn interatomic distances [19].…”
Section: Xrd Analysissupporting
confidence: 65%
See 3 more Smart Citations